Associations of different degrees and types of obesity with cardiovascular disease incidence among rural Kazakh residents in Xinjiang Uygur Autonomous Region - Jia HE; Hao-yue QI; Yu LI (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To analyze associations of different degrees and types of obesity with cardiovascular disease (CVD) incidence among rural Kazakh residents in Xinjiang Uygur Autonomous Region (Xinjiang) and to provide evidences for the prevention and control of CVD in Kazakh residents.Methods Prospective cohort design was adopted in the study including face-to-face interview with a self-designed questionnaire, physical examination and laboratory tests. A baseline survey was first conducted among 2 644 permanent rural Kazakh residents aged 18 years and above from April 2010 to December 2012 in a town of Xinjiang; a follow-up survey was then carried out among 2 286 participants during April - December 2016. ResultsThe follow-up survey was completed among a total of 2 004 participants (796 males and 1 208 females averagely aged 40.72 ± 12.35), with an accumulated follow-up of 11 001.96 person-years and a median follow-up of 5.49 years. Of the participants followed-up, 495 (24.7%), 259 (12.9%) and 881 (44.0%) were identified with overweight, obesity and central obesity. During the follow-up period, totally 278 CVD incidents were observed and the cumulative incidence rate of CVD was 13.9% among all the participants; the cumulative incidence rate of CVD was 10.2%, 17.6%, and 24.7% among the participants with normal weight, overweight, and obesity; while among the participants with and without central obesity, the cumulative incidence rate of CVD was 20.0% and 9.1%, respectively. After adjusting for confounders such as gender, age, education, occupation, smoking, alcohol drinking, hypertension, metabolic syndrome, blood glucose, blood lipid, consumption frequency of light-colored vegetables/milk and milk products/animal viscera/fresh meat, Cox proportional hazard regression analysis revealed that the risk of CVD incidence increased significantly among the participants with overweight (relative risk [RR] = 1.76, 95% confidence interval [CI]: 1.34 - 2.31) and obesity (RR = 2.36, 95% CI: 1.74 - 3.20) compared to that among those with normal weight; the risk of CVD incidence also increased among the participants with central obesity (RR = 2.23, 95% CI: 1.75 - 2.85) in comparison with that among those without central obesity. ConclusionAmong rural Kazakh residents in Xinjiang, the incidence rate of CVD is relatively high and overweight, obesity and central obesity could increase the risk of CVD incidence.